Socialization Trouble. European Populist States and Compliance with Human Rights Norms - Tacik, Przemyslaw (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional, 2021)
This paper aims to reconceptualize the theoretical frameworks that underpin paradigms of the theory of socialization in international and European law. The somewhat carefree optimist approach to the compliance with international human rights norms, based on the assumption that within the European Union (EU) the victory of the liberal paradigm of human rights is unquestionable and self-evident, dominated the previous decade. Socialization paradigms applied to Central, Eastern, and Southeastern European countries understood this process as mostly unidirectional and based on a clear “teacher-student” relationship. However, with the rise to power of Hungarian Fidesz, this uplifting conviction was shadowed by first doubts. Hungarian populism at power demonstrated the first traits of the future complex set of strategies applied, among others, in Poland, Romania and Italy. The independence of the law as a human rights guarantee was challenged not only practically, by pursuing political goals through violation or circumvention of valid norms, but also theoretically, by the doctrine of the “illiberal state” first heralded by the Hungarian Prime Minister Viktor Orbán. Even though these transformations encountered responses from European institutions, it was neither prompt nor effective. Soon enough Hungary as the enfant terrible of the EU was joined by further countries of the EU. The Court of Justice of the European Union (CJEU) and the European Court of Human Rights (ECtHR) reacted to the increase of human rights violations, but they are deprived of an entitlement to address “illiberal democracy” in a systemic manner. Consequently, the populist revolt against the very concept of human rights requires a much broader and complex assessment. Its strength consists in the focus of effective state (and party) power coupled with rhetorical strategies against human rights and its mechanisms of protection. In this paper, I confront socialization paradigms with the crisis of human rights protection brought about by the populist wave. I argue that in order to address this crisis adequately, the blind spots of previous socialization paradigms need to be recognized and overcome.